POST-HARVEST TECHNOLOGY: THE USE OF CONTROLLED ATMOSPHERE STORAGE TO EXTEND THE SHELF LIFE AND MAINTAIN THE QUALITY OF MANGOSTEEN - Suhartin Dewi Astuti; Chenda Dara (Techno Agriculturae Studium of Research, 2025)
Mangosteen (Garcinia mangostana), known as the “queen of fruits,” is a highly perishable tropical fruit with a short shelf life. Post-harvest losses due to poor storage and handling are significant challenges, especially for export markets. Controlled atmosphere (CA) storage, which modifies oxygen, carbon dioxide, and humidity levels, has been identified as a promising technology for extending the shelf life of fruits while maintaining their quality. However, limited research has been conducted on the application of CA storage for mangosteen in tropical climates like Indonesia. This study aims to explore the use of controlled atmosphere storage to extend the shelf life and preserve the quality of mangosteen fruits. The research focuses on determining the optimal storage conditions for mangosteen using CA technology and assessing its impact on fruit quality parameters such as color, texture, firmness, and overall freshness. A laboratory-based experimental design was employed, where mangosteen fruits were stored under various controlled atmosphere conditions (oxygen, carbon dioxide, and temperature). The fruits were periodically evaluated for changes in quality parameters using standard techniques, including firmness testing and sensory evaluation. The results indicate that CA storage effectively extended the shelf life of mangosteen by up to 15 days compared to the conventional storage method. The fruits stored under optimal CA conditions showed minimal loss in firmness, color retention, and overall freshness. In conclusion, controlled atmosphere storage is a promising solution for extending the shelf life and maintaining the quality of mangosteen, making it a viable option for improving post-harvest management and enhancing marketability in export markets.